Legal Regulation of the Condition of Ownership/Possessions Inalienability: A Comparative Critical Analysis - Rashid, Tarek Gomaa Al-Sayed; Hassan, Khaled Gamal Ahmed; Al-Khal, Reem Abdulatif; Al- Sayed, Abdulrahman Hashim (Journal of Posthumanism, 2025)
As a general principle, property owners have the right to freely manage their property, and this freedom should not be restricted. However, some Arab legislations have permitted provisions that prevent owners from exercising this right to serve a legitimate interest that may take precedence. Such restrictions should be temporary rather than permanent, and could be supported by strong, legitimate justifications. This research employs a comparative analytical approach to examine the legal framework surrounding inalienability conditions, aiming to clarify the true nature of such conditions and differentiate them from similar concepts. We will explore the perspectives of jurisprudence, the judiciary, and legislative bodies regarding this condition and the necessary requirements for its validity; otherwise, it will be deemed null and void. Furthermore, we will assess how this condition can be invoked against third parties. Additionally, we will delineate the legal nature of this condition and the legal implications imposed by law on any acts that violate it. We will also evaluate the extent of a judge’s authority to correct a prohibitive condition rather than declaring it invalid. One of the key findings of this research is the necessity of amending certain provisions regarding conditions that prohibit disposition, allowing judges to rectify them in specific cases rather than automatically ruling them invalid.